2018
DOI: 10.1097/igc.0000000000001272
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Uterine Serous Carcinoma—A Multicenter Study

Abstract: Peritoneal cytology and myometrial invasion could be independent prognostic factors for 3-year DFSR, cumulative recurrence, and cumulative mortality of patients with USC. Prospective studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Overall, the 35% recurrence-rate we found in our cohort is well-comparable to what reported in previous studies [ 24 25 ]. In accordance with the most recent published literature, we found the presence of positive lymph node(s) at final histology the main adverse factor influencing both DFS and DSS [ 25 ], while the administration of chemotherapy and age were associated with poorer progression and survival outcomes, respectively. Moreover, the updated analysis of the PORTEC 3 [ 26 ], showed a significantly improved overall survival and failure-free survival with the use of chemotherapy in addition to radiotherapy especially in patients with USC.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the 35% recurrence-rate we found in our cohort is well-comparable to what reported in previous studies [ 24 25 ]. In accordance with the most recent published literature, we found the presence of positive lymph node(s) at final histology the main adverse factor influencing both DFS and DSS [ 25 ], while the administration of chemotherapy and age were associated with poorer progression and survival outcomes, respectively. Moreover, the updated analysis of the PORTEC 3 [ 26 ], showed a significantly improved overall survival and failure-free survival with the use of chemotherapy in addition to radiotherapy especially in patients with USC.…”
Section: Discussionsupporting
confidence: 91%
“…LVSI is an established prognostic factor in EC and should be accounted for as a possible confounding variable when evaluating other prognostic factors, such as the stage and impact of positive cytology. As such, a large multi-institutional report by Zhong et al evaluated the impact of cytology status on USC and also failed to account for LVSI; and also neglected to include the impact of any type of treatment in multivariate analysis ( Zhong et al, 2018 ). The study performed by Seagle et al also evaluated early stage EC of multiple histologies and found positive cytology was associated with decreased overall survival, even in low-grade EC, and that adjuvant chemotherapy was associated with increased survival ( Seagle et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In logistic regression analysis, only optimality was an independent significant factor for recurrence. In a multicenter uterine serous cancer study reported by Zhong et al, advanced stage, myometrial invasion, adnexal involvement, lymph node metastasis, and positive peritoneal cytology were stated as independently associated prognostic factors for the DFS, and these listed factors were also associated with disease recurrence (22) . However, in a single institution study of 62 uterine serous carcinoma cases it was found that positive peritoneal cytology, positive LVSI, positive lymph nodes, and adjuvant therapies were not statistically significant in survival analyses (23) .…”
Section: Discussionmentioning
confidence: 92%